Are you ready for the year 2000? (Public Management (00333611), 1997)
An excerpt from InfoTech Report, which is published by ICMA, Washington, D.C. Local governments that have automated their operations are facing a crisis because of the impending year 2000 dating problem. Having evaluated the extent of their particular problems, local governments need to decide whether to hire someone to remedy the problem, such as the software vendor or a private firm, or whether to tackle the problem themselves. Contracting out the evaluation and remediation can be costly, depending on the size and complexity of the operation. Details of how Potomac Electric Power Co., an electric utility in Washington, D.C., dealt with its year 2000 problem are provided.